Visualizing Shared Power: The Heraldry of Archdukes Albert and Isabella Clara Eugenia - Fernández Guisasola, Luis Fernando; Francisco Olmos, José María (Eikón / Imago, 2026)
This paper analyzes the evolution of Infanta Isabel Clara Eugenia and Archduke Albert in relation to their marital status and political position. It examines how, before their marriage, Albert used a coat of arms that emphasized his connection to the Hispanic Monarchy, reflecting his trajectory under the protection of Philip II. On the other hand, after Isabel Clara became the sovereign of the Netherlands, a coat of arms was established for her that highlighted her single status. After the marriage, they adopted a joint coat of arms, where the Austro-Burgundian elements became prominent, reflecting their shared sovereignty in the Netherlands. However, the individual use of this emblem suggests that the title belonged more to Albert. This interpretation in the coat of arms of Isabel Clara Eugenia as a widow, where she places their former joint arms where her husband’s should be, is explored. Through the study, it is demonstrated how the archdukes used heraldry as a visual representation of political and dynastic legitimacy, adapting to changes in power and reinforcing their position as sovereigns.